2013
DOI: 10.1177/0093854812467942
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Interaction between Level of Risk and Dosage of Treatment

Abstract: the risk principle suggests that effective correctional interventions should vary the intensity of treatment by offender risk, with higher risk offenders receiving more intense services than lower risk offenders. Although much research indicates that programs that target higher risk cases are more likely to be effective, relatively little research has examined the impact of varying levels of treatment dosage by risk. Consequently, this study seeks to identify the number of hours of treatment that are necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Given the high prevalence of destabilizers in this class, ancillary services might be needed to help foster desistance from offending for these individuals. Even if specific program content is not varied for this group, it might be efficacious to match these clients to more intensive and comprehensive forensic therapy programs (Polaschek, ) with increased dosage (Bourgeon and Armstrong, ; Crites and Taxman, ; Sperber, Latessa, and Makarios, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high prevalence of destabilizers in this class, ancillary services might be needed to help foster desistance from offending for these individuals. Even if specific program content is not varied for this group, it might be efficacious to match these clients to more intensive and comprehensive forensic therapy programs (Polaschek, ) with increased dosage (Bourgeon and Armstrong, ; Crites and Taxman, ; Sperber, Latessa, and Makarios, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study findings highlight the complexity of offender need profiles and the fact that one size cannot fit all when it comes to providing correctional interventions. This study builds on the growing body of literature that advances knowledge beyond the risk principle to consider, for example, the interaction between offender risk and program dosage (Sperber et al., , ; Taxman, Perdoni, and Caudy, ), the sequencing of interventions based of offender risk and readiness to change (Stephenson et al., ), and the tailoring of CBT programming to the risk and needs of the individual offender (Polaschek, ). Continuation of this line of inquiry is essential for maximizing the effectiveness of correctional treatment in practice.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of treatment dosage (the number of therapeutic hours required to effect change) has received some attention in the offender treatment literature of late, with suggestions that between 100 and 300 hr of treatment over an approximate 4-month period are necessary to effect positive change (e.g., Bourgon & Armstrong, 2005;Sperber, Latessa, & Makarios, 2013). Self-improvement is a complex process that involves an interaction between broad treatment and client variables that go beyond a prescribed number of treatment hours.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Nevertheless, optimizing correctional policy and practice rests on a more granular understanding of what works with offenders. Existing research has shown, for example, that increasing the length and dosage of treatment generally yields better recidivism outcomes, particularly for higher risk offenders (Lowenkamp, Latessa, and Holsinger, ; Sperber, Latessa, and Makarios, ), but there is also a point at which longer durations of treatment can produce diminishing returns (Duwe, ; Loughran et al, ; Wexler, Falkin, and Lipton, ).…”
Section: Resultsmentioning
confidence: 99%